2019
DOI: 10.1039/c8bm00970h
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity focused ultrasound (LIFU) triggered drug release from cetuximab-conjugated phase-changeable nanoparticles for precision theranostics against anaplastic thyroid carcinoma

Abstract: This study provides an efficient theranostic strategy for concurrent targeted ultrasound molecular imaging and effective synergistic antitumor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 74 publications
2
27
0
Order By: Relevance
“…It was also possible to image the droplets before activation using B-mode and contrast-enhanced ultrasound imaging, which can be seen in Figure 3. These results are similar to those obtained by Wang et al [87]. They developed a biocompatible cetuximab-conjugated phase-change capsules (H-CPN) that resulted in a cell viability for C643 cells of 23.5% ± 1.29% after 3 minutes of LIFU exposure, in comparison with a cell viability of 31.09% ± 1.57% for free 10-HCPT.…”
Section: Applications Of Acoustic Droplet Vaporizationsupporting
confidence: 89%
“…It was also possible to image the droplets before activation using B-mode and contrast-enhanced ultrasound imaging, which can be seen in Figure 3. These results are similar to those obtained by Wang et al [87]. They developed a biocompatible cetuximab-conjugated phase-change capsules (H-CPN) that resulted in a cell viability for C643 cells of 23.5% ± 1.29% after 3 minutes of LIFU exposure, in comparison with a cell viability of 31.09% ± 1.57% for free 10-HCPT.…”
Section: Applications Of Acoustic Droplet Vaporizationsupporting
confidence: 89%
“…However, the cell viability inhibition of FA-FCP + LIFU was significantly higher than that of FP + LIFU, FCP + LIFU and FA-FCP without LIFU, indicating that FA-FCP combined with LIFU irradiation offered better anti-tumor efficiency. This result was mainly due to the presence of LIFU and the acid environment of the lysosome, both of which could induce the drug release and cavitation effect, and the FA-mediated tumor cells target effect [36][37][38].…”
Section: In Vitro and In Vivo Anticancer Therapymentioning
confidence: 99%
“…In vitro release studies were performed using the dialysis bag method as reported. [ 28 ] HCaM‐PB and HSiM‐PB were added into a dialysis bag and placed in PBS solution (pH 7.4) for the first 12 h and in PBS (pH 5.0) for another 60 h at a rotation speed of 120 rpm min −1 and a temperature of 37 °C. At the predetermined time points, 1 mL of supernatant was taken and the cumulative drug release was determined by HPLC.…”
Section: Methodsmentioning
confidence: 99%